INNOVATIONS OF COMPUTER SCIENCE IN THE HIGH EDUCATIONAL SYSTEM - Dehqonova, Ohista; Taylanov, Nizom (Физико-технологического образование, 2022)
In this work we consider the problem of computer science teaching in high school system. Management activity is one of the components of the didactic process: when modeling lessons and extracurricular activities, when designing a lesson, when designing a lesson, when designing technological maps, when analyzing a completed educational process, control and evaluation tools (testing, computer test, self-assessment, etc.) is reflected in the process of diagnosing the results of the course.